2015
DOI: 10.2147/copd.s84436
|View full text |Cite
|
Sign up to set email alerts
|

LANTERN: a randomized study of QVA149 versus salmeterol/fluticasone combination in patients with COPD

Abstract: BackgroundThe current Global initiative for chronic Obstructive Lung Disease (GOLD) treatment strategy recommends the use of one or more bronchodilators according to the patient’s airflow limitation, their history of exacerbations, and symptoms. The LANTERN study evaluated the effect of the long-acting β2-agonist (LABA)/long-acting muscarinic antagonist (LAMA) dual bronchodilator, QVA149 (indacaterol/glycopyrronium), as compared with the LABA/inhaled corticosteroid, salmeterol/fluticasone (SFC), in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 42 publications
6
90
0
Order By: Relevance
“…In both the GOLD B and GOLD D subgroups, dual bronchodilation with IND/GLY demonstrated superior improvement in trough FEV 1 , weighted mean FEV 1 from 0 to 12 hours and peak FEV 1 versus SFC. These findings are consistent with previously reported trials, where IND/GLY showed a significant improvement in lung function versus SFC 6,7. Treatment differences in all the lung function parameters between IND/GLY and SFC were clinically significant in the overall pooled population and also in patients belonging to the GOLD B and GOLD D subgroups, except pre-dose trough FEV 1 in the GOLD D subgroup (treatment difference, 80 mL).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In both the GOLD B and GOLD D subgroups, dual bronchodilation with IND/GLY demonstrated superior improvement in trough FEV 1 , weighted mean FEV 1 from 0 to 12 hours and peak FEV 1 versus SFC. These findings are consistent with previously reported trials, where IND/GLY showed a significant improvement in lung function versus SFC 6,7. Treatment differences in all the lung function parameters between IND/GLY and SFC were clinically significant in the overall pooled population and also in patients belonging to the GOLD B and GOLD D subgroups, except pre-dose trough FEV 1 in the GOLD D subgroup (treatment difference, 80 mL).…”
Section: Discussionsupporting
confidence: 92%
“…This was not unexpected, since a similar finding was observed in the LANTERN,7 ILLUMINATE,6 and UMEC/VI (umeclidinium/vilanterol) versus SFC8 studies. Moreover, neither studies included in the analysis was powered to show the treatment differences in terms of patient-reported outcomes.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations